Analysis of factors affecting cash holding in mining companies on the IDX - Liniarti, Sri; Nasution, Rizky Surya Andhayani (Jurnal Mantik, 2024)
This study was conducted to examine the influence of net working capital and firm size, on cash holding in mining companies on the Indonesia Stock Exchange in 2018-2022. The sampling technique uses the purposive sampling method and data processing using SPSS software. In this study, there were 54 companies that were sampled from 120 companies and analyzed by multiple linear regression. The results of this study simultaneously show that firm size and net working capital have a negative but significant effect on cash holding, firm size has a negative and significant correlation on cash holding, while net working capital has a negative but not significant effect on cash holding